1981
DOI: 10.1002/eji.1830111207
|View full text |Cite
|
Sign up to set email alerts
|

Defective antigen presentation by macrophages from mice genetically selected for low antibody response

Abstract: Rome Mice, selected for high (H) and low (L) antibody responses to xenogeneic erythrocytes (Biozzi mice, selection I), have been tested for their immune responsiveness to lysozymes. The anti-ring-necked pheasant egg-white lysozyme (REL) and anti-hen egg-white lysozyme (HEL) primary plaque-forming cell responses are 20 to 40-fold lower in L than in H mice. The heterogeneity of anti-HEL antibodies in the secondary response, as analyzed by isoelectric focusing, is highly reduced in L as compared to H mice. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 23 publications
0
5
1
Order By: Relevance
“…3, B.lO.S and L-I M a did not differ in their ability to stimulate eight distinct T-T hybridomas in the presence of OVA. Our results differ from those of Adorini and Doria [7],who noted a difference in the capacity of HEL-pulsed M a of the H-I and L-I mice to stimulate HEL-primed F1 T cells.The H-25 haplotype of the L-I line, well known to be a low H-2 responder haplotype to HEL [lo], may explain this finding. Furthermore, in F1 mice there is a dominance of the response to the preferred haplotype (another Ir gene effect).…”
Section: Processing and Presentation Of Ova By Peritoneal Macrophagescontrasting
confidence: 99%
See 1 more Smart Citation
“…3, B.lO.S and L-I M a did not differ in their ability to stimulate eight distinct T-T hybridomas in the presence of OVA. Our results differ from those of Adorini and Doria [7],who noted a difference in the capacity of HEL-pulsed M a of the H-I and L-I mice to stimulate HEL-primed F1 T cells.The H-25 haplotype of the L-I line, well known to be a low H-2 responder haplotype to HEL [lo], may explain this finding. Furthermore, in F1 mice there is a dominance of the response to the preferred haplotype (another Ir gene effect).…”
Section: Processing and Presentation Of Ova By Peritoneal Macrophagescontrasting
confidence: 99%
“…Wiener and Bandieri [6] reported a significant difference in the retention of membrane-bound 12sII-KLH between the MQ from the H-I and L-I lines. Subsequently, Adorini and Doria [7] observed that hen egg lysozyme (HEL)-pulsed M@ from H-I mice were much more effective in stimulating HEL-primed F1 T cells than HEL-pulsed M@ from L-I mice. Both groups concluded that the difference in Ab responsiveness between the H-I and L-I lines could be explained at least in part by differences in Ag processing between the M@ of these two lines of mice.…”
Section: Introductionmentioning
confidence: 99%
“…This question has been further reconsidered in terms of Ag processing and presentation. Adorini & Doria [8] observed that Ag pulsed macrophages from HI were more effective than those of LI mice in stimulating primed (HI 2 LI) F1 T cells. However, the difference in I-A restriction between HI (H-2 q ) and LI (H-2 s ) may impair the significance of these results.…”
Section: Introductionmentioning
confidence: 99%
“…These two lines gave identical antibody responses to the somatic antigen of Salmonella used in Selection IV. Several studies have demonstrated that the selective breeding modifies macrophage function in an opposite direction to that of antibody production for Selections I, II and IV-A (1,5,7,17,21). Macrophages of L mice presented high catabolism of the immunogens with consequent deficiency in their antigen presentation function leading to a low antibody production.…”
mentioning
confidence: 99%